The Effect of Some Climatic Variables and Frosts Waves on Citrus Crops - Alhader, Moshabab M; Hafez, Mohammed S (Al-Adab Journal, 2021)
This study examined the effect of some climatic variables and their role in growing citrus fruits in northern Saudi Arabia, which showed that low temperatures accompanied by calm winds and high relative humidity as well as creeping air masses are among the most important factors that contribute to the worsening of frost. This study also dealt with hourly frost waves - a case study - based on the study of climatic data of the study area stations for one day of frost waves that occurred in the study area for the year 2008.